Enhancing Tourism Promotion Through Digital Public Relations: A Case Study in Sleman, Yogyakarta - Devika Nur Khoirunnisa; Lukman Hakim (LPPM Stikosa - AWS, 2025)
The Sleman Tourism Office serves as the coordinator in the process of tourism development in the Sleman area. In promoting the destinations and potential there, the Tourism Office is aware of the effects of using existing digital technology and utilizes these advantages to boost the potential there. The purpose of this research is to find out the extent of the role of digital public relations of the Tourism Office and the extent of the development of digital public relations in Sleman tourist villages. This research uses a qualitative approach with a case study approach, and uses the 4 Steps PR Theory in analyzing the data obtained. The results of this study indicate that the utilization of digital public relations carried out by the Sleman Tourism Office has implemented several strategic steps of digital public relations, but there are several steps that need to be improved and more supervision on the obstacles that occur. The Sleman Tourism Office carries out a collaboration post strategy in dealing with this obstacle. In addition, the utilization of digital public relations has also been carried out by both Grogol Tourism Village and Gamplong Tourism Village. Through the Instagram platform, these two tourist villages promote their local potential.